Cardiovascular autonomic dysfunction in “Long COVID”: pathophysiology, heart rate variability, and inflammatory markers - Marques, Karina Carvalho; Quaresma, Juarez Antônio Simões; Falcão, Luiz Fábio Magno (Frontiers in Cardiovascular Medicine, 2023)
Long COVID is characterized by persistent signs and symptoms that continue or develop for more than 4 weeks after acute COVID-19 infection. Patients with Long COVID experience a cardiovascular autonomic imbalance known as dysautonomia. However, the underlying autonomic pathophysiological mechanisms behind this remain unclear. Current hypotheses include neurotropism, cytokine storms, and inflammatory persistence. Certain immunological factors indicate autoimmune dysfunction, which can be used to identify patients at a higher risk of Long COVID. Heart rate variability can indicate autonomic imbalances in individuals suffering from Long COVID, and measurement is a non-invasive and low-cost method for assessing cardiovascular autonomic modulation. Additionally, biochemical inflammatory markers are used for diagnosing and monitoring Long COVID. These inflammatory markers can be used to improve the understanding of the mechanisms driving the inflammatory response and its effects on the sympathetic and parasympathetic pathways of the autonomic nervous system. Autonomic imbalances in patients with Long COVID may result in lower heart rate variability, impaired vagal activity, and substantial sympathovagal imbalance. New research on this subject must be encouraged to enhance the understanding of the long-term risks that cardiovascular autonomic imbalances can cause in individuals with Long COVID.